2006
DOI: 10.1097/01.rli.0000223742.35655.24
|View full text |Cite
|
Sign up to set email alerts
|

Brain Magnetic Resonance Imaging at 3 Tesla Using BLADE Compared With Standard Rectilinear Data Sampling

Abstract: PROPELLER (BLADE) brain magnetic resonance imaging is also applicable at 3 T. In addition to minimizing motion artifacts, the PROPELLER acquisition scheme reduces other magnetic resonance artifacts that would otherwise degrade scan quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 18 publications
3
64
0
Order By: Relevance
“…There have been no previous reports comparing SNR between cVIBE and rVIBE in a phantom study. Although the reasons for the higher SNR with rVIBE are unclear, the reason can be explained by the repeated acquisition around the center of k-space compared with standard Cartesian k-space readout, and uncorrected higher frequency data in kx-ky because of cylindrical shape of stack-of-stars trajectory [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…There have been no previous reports comparing SNR between cVIBE and rVIBE in a phantom study. Although the reasons for the higher SNR with rVIBE are unclear, the reason can be explained by the repeated acquisition around the center of k-space compared with standard Cartesian k-space readout, and uncorrected higher frequency data in kx-ky because of cylindrical shape of stack-of-stars trajectory [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…T 1 -FLAIR-BLADE could not achieve higher image quality scores than T 1 -SE in a small minority of cases, perhaps because of the occasional generation of another unique artifact by BLADE (wrap artifact 6 ), especially in those cases with severe head motion (Fig. 2).…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…On T 1 -SE images, the border between the gray and white matter of the cerebellum tends to be aŠected by a pulsation artifact from the sigmoid sinus. Previous clinical studies have shown that a BLADE acquisition can reduce pulsation artifacts from the transverse and sigmoid sinuses at T 2 -FLAIR imaging 6 and contrast-enhanced T 1 -FLAIR in adults. 8 The reduction of this artifact from the venous sinus was also achieved in non-contrast-enhanced T 1 -FLAIR-BLADE in children.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
See 2 more Smart Citations